Investigation of The Awareness Level in Malaysia’s Manufacturing Industries on the Implementation of Industry 4.0 - Effendi Mohamad; M.S Abd Rahman; A.A Abdul Rahman; N Mohamad; N.A.A Nor Azlan; Adi Saptari (JIE Scientific Journal on Research and Application of Industrial System, 2021)
In this study, the researchers aimed to investigate the awareness of the Malaysian manufacturing industries with regards to the implementation of the Industry 4.0 concept and also determine its levels. Different sectors of the Malaysian manufacturing sector like the Government Link Companies (GLCs), Small and Medium-scale Enterprises (SMEs), and other national or Multinational Corporations (MNCs) were included in this study. The researchers applied a survey-based research methodology and their sample size consisted of 91 Malaysian corporations. The participants in this study comprised of the managers and employees, as company representatives, and they were asked to complete the questionnaire and participate in the interview. The results of the survey showed that around 50.5% of respondents were aware and familiar with the Industry 4.0 regulations. Also, according to the survey results, the awareness regarding the Industry 4.0 regulations was mainly due to the foreign sectors including the multinational corporations like the electrical and electronic industries which contained several advanced assets and increased productivity. These results were very helpful for further research, especially for creating a future framework that could assimilate the ideas related to Industry 4.0 amongst the various other Malaysian industries belonging to the manufacturing sector.